Gamification of Faraid Science: Development of Digital Teaching Materials to Improve Inheritance Calculation Skills - Zuhri, Saefudin; Hidayat, Sholeh; Fadlullah, Fadlullah (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study seeks to create and enhance educational game-based teaching learning material on Islamic inheritance law via HIWAR, intended as supplementary resources and learning media for students specializing in Islamic Education. This study was undertaken in 2025 with a cohort of students majoring in Islamic Education at UIN Sultan Maulana Hasanuddin Banten, recruited using selective sampling. This study was incorporated into the Dick and Carey Research and Development framework. The validation results from experts, including media, learning material, and language specialists, indicated that the Indonesian language game-based teaching learning material is valid for use, with average validation scores of 91.5% from media experts, 92.5% from learning material experts, and 92% from language experts. The one-to-one evaluation phase yielded an average score of 4.6, the small group average was 4.8, and the field test average also reached 4.8, all classified as very good. The effectiveness test of the instructional learning material, involving 30 students, utilized the N-Gain Score Test, yielding an N-Gain Score of 0.7515 for the experimental class and 0.6450 for the control class. An Independent Sample t-Test revealed a significant difference in the enhancement of understanding the concept of heredity between students exposed to conventional teaching learning material and those utilizing interactive teaching learning material The findings suggest that readers utilize “HIWAR” game-based inheritance teaching learning material as an alternative to enhance inheritance calculating abilities and comprehension of inheritance concepts in Islamic higher education courses on inheritance. These developmental outcomes can be further enhanced by educators or other stakeholders.